Paradyplomacja regionalna w obszarze południowego Bałtyku na przykładzie stosunków transgranicznych Województwa Zachodniopomorskiego - H.Toszek, Bartłomiej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
Individual and group transborder cooperation of theWestern Pomeranian Province with other South Baltic regions is in line with a pan-European trend of regional authorities becoming independent and participating in international relations as independent entities. This ‘paradiplomacy’ is undoubtedly a factor that contributes to the relativization of the state as a traditional arena of political activity. Simultaneously, as the subsidiarity principle, which is the foundation of EU regional policy, is becoming increasingly popular, it seems unavoidable and irreversible that regional structures will be vested with increasing powers in the realm of foreign policy (that used to be reserved for national organs exclusively). In this context the collaboration of theWestern Pomeranian Province with other South Baltic regions is only at the beginning of a potential process to form its own ‘paradiplomacy’ as it remains constricted in the formula of state limitation and supervision. Therefore, at present it is unfeasible for Polish regional authorities, including the self-government ofWestern Pomerania, to conduct independent ‘paradiplomacy.’